INVASION OF ZEBRA MUSSEL DREISSENA POLYMORPHA PALLAS,1771) INTO THE COOLING SYSTEM WATER SUPPLY OF AL-MUSAYAB THERMAL POWER PLANT / IRAQ - JAWEIR, H.J.J.; AL-RAWI, T.R.; AL-NAKEEB, N.A. (Iraqi Journal of Aquaculture, 2022)
Zebra mussels Dreissena polymorpha are tiny bivalve mollusca , invade water supply of cooling system unit in Al- Musayab power plant, 60 km south-west Baghdad and grow to dense clusters. Its ability to rapidly colonize intake structures, such as pipes and screens causing reduction in water pumping capabilities .Some biological aspects of zebra mussel Dreissena polymorpha have been studied and some physical & chemical parameters were examined as alimenting factors for the species Samples collecting was done monthly from two sites within the water system , the first was the traveling band screen (TBS ) and the other site was small canal collecting excess water passing from TBS .Biological studies revealed that the samples collected from the canal includes five size groups with average length of 5.7 ; 11.3 ; 16.7 ; 21.9 & 27.3 mm. In TBS , the individuals found all over the year with highest number of 135 individuals recorded in August . Individuals of a length of 11.3 & 16.7mm were the dominant.In general, from total number of 799 individuals collected from TBS, 388 individuals were of size of 11.3mm and 239 individual were of size 16.7mm while no large specimens of large size group of 27.3mm were recorded in TBS.To study the settlement rate of larvae, several concreat tiles of (25X25cm) were suspended at depths of 2,4& 6 m. in the sedimentation pond (12m depth). The number of juveniles were counted monthly . The result showed that there were two peaks of settlement , one in June and the other in September and October .Depth of 6m was the most suitable for settlement.The average length of settled juveniles ranged between 3.5-6.1mm. Water temperature in the site ranged between 11-32o C , Dissolved oxygen was 4.8-8.3ml/L . The highest value of turbidity was 49NTU.Ca++ was 68-136mg/l and Mg++ was 34- 72mg/l